Size and determinants of the shadow economy in Nigeria: Evidence from a monetary approach - Tari M. Karimo; Mohammed M. Tumala; Ibrahim U. Wambai (CBN Journal of Applied Statistics, 2022)
This study investigates the size and determinants of the shadow economy in Nigeria. It adopts an aggregation approach within the monetary framework and utilises the ARDL estimation technique to analyse quarterly data from 2010 Q1 to 2019 Q4. On average, the results suggest that the quarterly size of the shadow economy is about 55 per cent of the country's GDP. The findings show that government size reduces the size of the shadow economy in the short run but increases it in the long run. The study also finds that interest rate, which is the opportunity cost of holding cash, and development of digital payment system (financial innovation) disincentivise informality. The policy implication is that the continuous development of effective digital payment products and their use could potentially reduce the size of the shadow economy in Nigeria.
Keywords: E26; E41; E43; 330; Aggregation approach; interest rate; government size; monetary framework; shadow economy